THE INFLUENCE OF LEARNER AUTONOMY ON EFFECTIVE EDUCATIONAL OUTCOMES IN HIGHER EDUCATION - Abdirakhimova Mokhigul Normurodovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article explores the theoretical and pedagogical significance of learner autonomy in higher education. Learner autonomy is considered a key factor in modern education, emphasizing students’ ability to take responsibility for their own learning process. The study is based on a qualitative analytical approach involving the review of scientific literature in pedagogy and educational psychology. The findings indicate that learner autonomy enhances cognitive engagement, critical thinking, and self-regulated learning skills. The study concludes that integrating autonomy-oriented strategies into educational frameworks improves the overall effectiveness of teaching and learning processes.